Distinguishing natural evolution and human impact on estuarine morpho-sedimentary development: A case study from the Vilaine Estuary, France - Traini, C. (Academic Press, 2015)
Estuaries are coastal areas controlled by hydrodynamic factors such as sea-level changes, waves and tidal currents, and river discharge. This study focuses on the Vilaine Estuary which is strongly impacted by human activity after construction of Arzal dam in 1970. The purpose of this research is to differentiate the role of natural from anthropogenic factors on sediment dynamics within the Vilaine Estuary. We are proposing a hypothetical model based on the hydrodynamic modification and morpho-sedimentary development by analyzing the natural estuarine evolution and the impact of human alteration to the natural system by utilizing datasets including river discharge, tidal currents, winds and wave activities to further combine with photographic, bathymetric, topographic and sedimentary surveys. Results show that waves carry sediment from the sea and rework local sediments. The river damming is reducing the tidal prims and leads to the fall of tidal currents. This new situation supports the sediment deposition and reduces at the same time the accommodation space which decrease tidal currents in feed-back. The Vilaine Estuary is therefore coming close to a bay-type functioning which leads to a channel narrowing, a drastic increase of the tidal flat zone, an acceleration of erosional processes affecting the main channel, salt marsh and all associated depositional systems. We propose a hypothetical model showing that this evolution took place in two steps and we show that the dam has an effect to accelerate a natural infilling of the estuary. Â© 2015 Elsevier Ltd.